2009
DOI: 10.1080/10407780902720841
|View full text |Cite
|
Sign up to set email alerts
|

Validation of DES-SST Based Turbulence Model for a Fully Developed Turbulent Channel Flow Problem

Abstract: This work discusses simulations using the detached eddy simulation based (DES) turbulence model to investigate turbulent channel flows. Applicability of Strelets' (2001) version of the DES model was tested for a fully developed turbulent channel flow problem in a rectangular duct. The unsteady Navier-Stokes equations were solved numerically at Reynolds number, Re s , of 180, 590, and 2000, respectively, and compared to results obtained using direct numerical simulation (DNS) and previously published DES data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The earlier DNS [23] indicated that turbulent statistics along the wall-bisectors agrees well with measured channel data of plane channel flow [35][36][37][38], despite the influence of the sidewalls in the former flow. For higher Reynolds number turbulence, it seems that large eddy simulation is better, and evidence can be found in previous works [39][40][41][42][43][44][45][46][47]. This paper presents the numerical results of turbulent largescale motion based heat and fluid flows in a SSD at various Reynolds numbers in the range from 10 4 to 10 6 at a given grid resolution with a grid number of about 1:2 Â 10 6 .…”
Section: Introductionmentioning
confidence: 72%
“…The earlier DNS [23] indicated that turbulent statistics along the wall-bisectors agrees well with measured channel data of plane channel flow [35][36][37][38], despite the influence of the sidewalls in the former flow. For higher Reynolds number turbulence, it seems that large eddy simulation is better, and evidence can be found in previous works [39][40][41][42][43][44][45][46][47]. This paper presents the numerical results of turbulent largescale motion based heat and fluid flows in a SSD at various Reynolds numbers in the range from 10 4 to 10 6 at a given grid resolution with a grid number of about 1:2 Â 10 6 .…”
Section: Introductionmentioning
confidence: 72%
“…Similarly, the detached eddy simulation (DES), has also been used for the modification of hybrid RANS-LES approach [62][63][64][65]. Since the LES was computationally too expensive for practical applications, a two-layer model is used, where in the wall region RANS-type calculations are performed for attached boundary layer, and then at a specified distance from the wall, the computation switches to LES for the detached large eddy.…”
Section: Turbulence Closuresmentioning
confidence: 99%
“…Some researches of DES, such as Strelets [64] and Home et al [65], have switched RANS and LES by utilizing the concept of Menter's SST [66], which blends k-ε and k-ω model for different zone. The filter is placed on the destruction term in the transport equation for the turbulent kinetic energy k…”
Section: Turbulence Closuresmentioning
confidence: 99%